1989
DOI: 10.1139/z89-252
|View full text |Cite
|
Sign up to set email alerts
|

Survival of certain naturally acquired freshwater parasites of juvenile sockeye salmon, Oncorhynchus nerka (Walbaum), in hosts held in fresh and sea water, and implications for their use as population tags

Abstract: Sockeye salmon (Oncorhynchus nerka) smolts were captured from the outlet streams of Cultus Lake, British Columbia, in 1985 and 1986, and from Fraser Lake, British Columbia, in 1986. Samples collected in 1985 were reared in salt water. Samples collected from each lake in 1986 were divided equally into two groups: one group was reared in fresh water, the other was maintained in salt water. Initially biweekly, and later monthly, subsamples from each group were examined for seven parasite taxa: Myxidium salvelini,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
1
21
1
Order By: Relevance
“…Unsegmented Eubothrium sp. (in fresh water) was observed by Bailey et al (1989) in sockeye salmon kept in the laboratory for 8 months without any possibility for new infections, which is in accordance with the findings of the present study. All salmon used in the present study were experimentally infected by procercoids at the same time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unsegmented Eubothrium sp. (in fresh water) was observed by Bailey et al (1989) in sockeye salmon kept in the laboratory for 8 months without any possibility for new infections, which is in accordance with the findings of the present study. All salmon used in the present study were experimentally infected by procercoids at the same time.…”
Section: Discussionsupporting
confidence: 93%
“…This study suggests that the two life cycles may not be completely separate. This is also supported by the fact that E. crassum has been observed to survive in sockeye salmon smolts for 7 months (Bailey et al 1989) and in salmon smolts for at least 3 months after sea water transfer (pers. obs.).…”
Section: Resultsmentioning
confidence: 65%
“…and Proteocephalus sp. and the acanthocephalan Neoechinorhynchus salmonis in intestine were observed between the host sockeye salmon (O. nerka) smolts held in freshwater or saltwater (Bailey et al, 1989). In freshwater at 10 C, the endohelminth Anisakis larvae when removed from the host and the nematode cysts in vitro can survive more than 2 mo (Mö ller, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…A long stay would reduce survival of the freshwater parasites in salt water or marine parasites in freshwater. The mean intensity of 1 freshwater ectoparasite and 2 endoparasites in Oncorhynchus nerka decreased when reared in seawater for 32-40 wk (Bailey et al, 1989). Survival time of the nematode larva Anguillicoloides crassus in intermediate and paratenic hosts was maximal in freshwater and declined with an increase in salinity (Kirk et al, 2000).…”
mentioning
confidence: 98%
“…Margolis and Boyce (1969), Moller (1976), and Bailey et al (1989) observed the longevity of parasite infections in fish in the laboratory, and their results can be used as a guide to the likely longevity of certain parasites in the field.…”
Section: Criteria For Suitable Parasite Tagsmentioning
confidence: 99%